Bentuk dan Efektivitas Dakwah di TVRI Kalimantan Timur - Syobah, Sy. Nurul (LP2M IAIN Samarinda, 2015)
Television is a technology product which becomes the need of human being. It becomes an important part of human life from morning up to the next morning. It is important, since it becomes an effective media to promote education, information, entertainment, and social connection. This is a descriptive qualitative research with communicative and management approach which aims at describing the effectiveness of da’wah in TVRI Kalimantan Timur. The findings of the study shows that there are two kinds of da’wah in TVRI, they are: 1) integrative da’wah which consists of the da’wah in the da’wah and non-da’wah program, 2) partial da’wah which is done by da’wah in the process of production and in the process of broadcasting. To measure the effectiveness of da’wah, it was done by doing a survei to the TVRI viewers. The result shows that da’wah in TVRI is not effective yet, since it has some flaws and weaknesses. Most of viewers state that the program should be improved by developing the quality of da’wah program in TVRI. TVRI has done and tried hard to create the program, yet it still needs to be improved and produce a qualified da’wah program.